Hubungan Keterlibatan Orang Tua dengan Prestasi Belajar Siswa - Santika Santika; Hasmi Syahputra Harahap (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research aims to determine parental involvement with the learning achievement of class X Science students at MAS Alliful Ikhwan Setia Abang Adik, South Labuhanbatu Regency. The research method used is a quantitative approach with a descriptive quantitative research type. The total sample was 48 students obtained using total sampling technique. The results of the research show that parental involvement is closely related to student learning achievement in class as evidenced by the questionnaire percentage value of 68.75% and the sample average learning outcome percentage value of 64.58%. The results of hypothesis testing show that the significance value is smaller than the probability value, namely p < 0.05, namely 0.000 < 0.05 and the correlation value of 0.604 or 36.48% has an influence on student learning outcomes and achievement. In conclusion, there is a significant relationship between parental involvement and student achievement at school. Keywords: Parental Involvement, MAS Alliful Ikhwan, Learning Achievement